Assessment of Workplace Hygiene among Contractual Workers in the Steel and Power Industry of Odisha, India - Parthsarathi Dehury; K Anil Kumar; Ranjit Kumar Dehury (Wolters Kluwer Medknow Publications, 2022)
Background: Workplace hygiene is vital in controlling infectious diseases in industries. The factors like unhealthy environment, unhygienic workplace, and contact between healthy and disease-affected employees cause industrial hazards in workplaces. Objectives: This study assessed various components of workplace hygiene among industrial workers. Materials and Methods: A quantitative survey has been conducted in a steel, and power industry limited in Odisha. The study surveyed 425 male contractual workers for primary data on workplace hygiene. Probability proportion to sample technique adopted for justification of the sample. The univariate and bivariate analysis models have been done according to the study's objective. Results: Nearly 92% of respondents reported proper use of washing facilities, and 97% used toilet and urinal appropriately. One-fourth of respondents use personal disinfected clothing, and 92.2% have access to safe drinking water. The factors such as education, technical education, and occupation are significantly associated with respondents' use of washing facilities, dining hall, personal protective clothing, safe drinking water, proper cleaning, and sanitation at the workplace. Conclusion: Workplace hygiene strengthens the safety measures at the workplace and reduces the incidences of occupational hazards.